Cooperative Recognition of Internationally Disseminated Ceftriaxone-Resistant Neisseria gonorrhoeae Strain - Lahra, Monica M.; Martin, Irene; Demczuk, Walter; Jennison, Amy V.; Lee, Ken-Ichi; Nakayama, Shu-Ichi; Lefebvre, Brigitte; Longtin, Jean; Ward, Alison; Mulvey, Michael R.; Wi, Teodora; Ohnishi, Makoto; et al. (Emerging infectious diseases, 2018)
Ceftriaxone remains a first-line treatment for patients infected by Neisseria gonorrhoeae in most settings. We investigated the possible spread of a ceftriaxone-resistant FC428 N. gonorrhoeae clone in Japan after recent isolation of similar strains in Denmark (GK124) and Canada (47707). We report 2 instances of the FC428 clone in Australia in heterosexual men traveling from Asia. Our bioinformatic analyses included core single-nucleotide variation phylogeny and in silico molecular typing; phylogenetic analysis showed close genetic relatedness among all 5 isolates. Results showed multilocus sequence type 1903; N. gonorrhoeae sequence typing for antimicrobial resistance (NG-STAR) 233; and harboring of mosaic penA allele encoding alterations A311V and T483S (penA-60.001), associated with ceftriaxone resistance. Our results provide further evidence of international transmission of ceftriaxone-resistant N. gonorrhoeae. We recommend increasing awareness of international spread of this drug-resistant strain, strengthening surveillance to include identifying treatment failures and contacts, and strengthening international sharing of data.